Treatment Options for Cancer Patients Suffering from Oral Mucositis - Chaudhry, Sharjeel (2023)
More than 75% of those receiving chemotherapy will experience oral mucositis, which is a major problem for both patients and carers. Lesions form in the digestive tract when chemotherapy drugs attack the rapidly dividing cells there. Tissue alterations might range from being completely painless to so severe as to cause bleeding, prevent oral intake, and need narcotic pain medications. Chemotherapy treatment is often postponed when oral mucositis is present. To better clearly categorise the symptoms linked with this condition, many assessment scores have been devised. Very few pharmaceutical therapies for oral mucositis, either to prevent its onset or to alleviate its symptoms, have been approved. Given the advancements in other areas of supportive care for chemotherapy patients, research into oral mucositis should be prioritised. This review will provide the management of oral mucositis in patients with cancer.